PENGARUH DISIPLIN, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL PURI SARON BARUNA BEACH COTTAGES - Umadeta Dewi, Nyoman Ichi; Srikasih, Ni Luh (Komunitas Manajemen Kompetitif, 2024)
This research aims to find out whether discipline, motivation and work environment influence the performance of Puri Bagus Saron Baruna Beach Cottages Hotel employees. This research was conducted at the Puri Bagus Saron Baruna Beach Cottages Hotel. The population used in this research were all employees who worked at the Puri Bagus Saron Baruna Beach Cottages Hotel, namely 37 employees. The measurement scale uses a Likert scale and then the data obtained is processed using multiple linear regression analysis techniques. In this research, the results obtained are 1) Discipline has a positive and significant effect on the performance of Puri Bagus Saron Baruna Beach Cottages Hotel employees with the t test results on the Work Motivation variable showing a calculated t value of 2.550 > from t table 1.687 and a significance value of 0.013 < 0.05 2) Motivation has no effect on the performance of Puri Bagus Saron Baruna Beach Cottages Hotel employees with the results of the t test on the Motivation variable showing a calculated t value of -0.852 < from t table 1.687 and a significance value of 0.401 > 0.05 3) The work environment has no effect on employee performance Hotel Puri Saron Baruna Beach Cottages with the t test results on the Work Environment variable shows a calculated t value of -0.057 < from t table 1.687 and a significance value of 0.955 > 0.05.